Patterns of Communication Among Marketing, Engineering and Manufacturing—A Comparison Between Two New Product Teams - Griffin, Abbie; Hauser, John R. (Management Science, 1992)
Models and scientific evidence suggest that firms are more successful at new-product development if there is greater communication among marketing, engineering, and manufacturing. This paper examines communication patterns for two matched product-development teams where the key difference between the groups is that one used a phase-review development process and the other used Quality Function Deployment (QFD), a product-development process adopted recently at over 100 United States and Japanese firms. To our knowledge, this is the first head-to-head comparison of traditional U.S. product development processes with QFD. Our data suggest that QFD enhances communication levels within the core team (marketing, engineering, manufacturing). QFD changes communication patterns from “up-over-down” flows through management to more horizontal routes where core team members communicate directly with one another. On the other hand, the QFD team communicates less on planning information and less with members of the firm external to the team. If this paucity of external communication means that the team has the information it needs for product development, and the QFD process has provided an effective means for moving the information through the team, it is a positive impact of QFD. If the result means that QFD induces team insularity, even when the team needs to reach out to external information sources, it is a cause for concern.